2021
DOI: 10.1111/jce.15254
|View full text |Cite
|
Sign up to set email alerts
|

Intraprocedural PRAETORIAN score for early assessment of S‐ICD implantation: A proof‐of‐concept study

Abstract: Introduction:The PRAETORIAN score (PS) was developed to assess the implant position and predict defibrillation success of the subcutaneous implantable cardioverter defibrillators (S-ICD). The main critique moved to the routine use of PS has been its postprocedural timing, that limits its usefulness on procedure guidance. The aim of this proof-of-concept study was to assess the feasibility of an intraprocedural use of PS.Methods: Forty consecutive patients undergoing S-ICD implantation were enrolled.Intraproced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The PRAETORIAN score was collected as per existing definition, either from a two-projection post-procedural chest X-ray or intra-procedurally. 17–19 Baseline device programming setup and the rate of SMART Pass algorithm use for inappropriate shock risk reduction 20 were collected as well. Follow-up strategy was left to each centre’s policy, with most patients being evaluated at 1, 6, and 12 months and every 6 months thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…The PRAETORIAN score was collected as per existing definition, either from a two-projection post-procedural chest X-ray or intra-procedurally. 17–19 Baseline device programming setup and the rate of SMART Pass algorithm use for inappropriate shock risk reduction 20 were collected as well. Follow-up strategy was left to each centre’s policy, with most patients being evaluated at 1, 6, and 12 months and every 6 months thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…A score was validated on an independent cohort of S-ICD recipients [ 94 , 95 ], and it holds true even in obese patients [ 96 ]. Intraoperative calculation of the score was proved feasible [ 97 ]. But appropriate determination of the score is to some extent subjective, and may necessitate some form of training [ 98 ].…”
Section: Defibrillation Testingmentioning
confidence: 99%
“…Currently, the next step of research is ongoing, with the aim of skipping DFT entirely and substituting it with the score evaluation only (i.e., prospective validation of the score by randomizing to standard DFT or using only the score without conversion testing; the PRAETORIAN DFT study) [ 10 ]. Moreover, in a recent proof-of-concept study [ 17 ], the intraprocedural assessment of the score was found to be feasible.…”
Section: Introductionmentioning
confidence: 99%